What does dermoscopy tell us about nevus spilus? - Chhiti, Sokaina; Soughi, Meriem; Bouraqqadi, Oumaima; Douhi, Zakia; Elloudi, Sara; Baybay, Hanane; Mernissi, Fatimazahra (International Journal of Scientific Research and Management (IJSRM), 2023)
Introduction: Nevus spilus (NS) is a pigmented lesion characterized by multiple macules or pigmented papules within a pigmentation. Initially was described by Burkley in 1842, this nevus has since been the subject of numerous publications, especially with regard to the debates about the appearance of melanomas within the lesion, hence the interest of a dermoscopic examination of screening and monitoring.  Objectives: Our aim is to describe dermoscopic patterns of NS in a research-based case study. Materials and methods: This is a prospective and descriptive study of 20 patients collected in our training over a period of 1 year. Results: we collected 20 patients whose average age was 34,5 years with sex-ratio 0.17. Clinically, all nevi were localized confetti macular, for the majority of cases, at the level of the trunk and the extremities. On dermoscopy, the reticular pattern was the most frequent in 08 cases followed by the homogeneous pattern in 07 cases than the mixed pattern: homogeneous patterns - reticular and homogeneous-globular, reticular-granular giving a characteristic sparkler appearance without signs of atypia. One patient underwent a biopsy confirming the diagnosis. None of our patients presented with melanoma. Conclusion: Naevus spilus is a benign lesion. However, a melanoma can develop even if it is rare, hence the interest of an exhaustive and regular skin examination with recourse to dermoscopy, showing the atypical aspects requiring excision from the outset.